Citogenética de Quirópteros: métodos e aplicações - Varella-Garcia, Marileila [UNESP]; Taddei, Valdir Antonio [UNESP] (Sociedade Brasileira de Zoologia, 1989)
Information about standard karyotypes, G-band, C-band and Ag-NOR staining patterns and other chromosomal data are reviewed for species of the New World bats. Techniques for collecting and processing the specimens, for the preparation of G- and C-band chromosomes and for staining of nucleolus organizer regions are described. Systematic implication are also discussed.